Role of Immunoglobulins in Muscular Dystrophies and Inflammatory Myopathies - Farini, Andrea; Villa, Chiara; Tripodi, Luana; Legato, Mariella; Torrente, Yvan (Frontiers in Immunology, 2021)
Muscular dystrophies and inflammatory myopathies are heterogeneous muscular disorders characterized by progressive muscle weakness and mass loss. Despite the high variability of etiology, inflammation and involvement of both innate and adaptive immune response are shared features. The best understood immune mechanisms involved in these pathologies include complement cascade activation, auto-antibodies directed against muscular proteins or de-novo expressed antigens in myofibers, MHC-I overexpression in myofibers, and lymphocytes-mediated cytotoxicity. Intravenous immunoglobulins (IVIGs) administration could represent a suitable immunomodulator with this respect. Here we focus on mechanisms of action of immunoglobulins in muscular dystrophies and inflammatory myopathies highlighting results of IVIGs from pre-clinical and case reports evidences.